PENGARUH LOKASI, KELENGKAPAN PRODUK, DAN PELAYANAN TERHADAP KEPUTUSAN BERBELANJA KONSUMEN DI MINI MARKET SINAR JAYA - Murni, Yanti; Rahmanto, Rommy (Ensiklopedia of Journal, 2018)
The business development in the globalization era gives an impact in the tight competition and difficult for company can penetrate market. In order to deal with tight and rapid competition, every company is required to optimize the existing resources and to implement the right market strategy in order to win the competition so that it can survive and grow in tight and rapid business competition right now. The research aims to test the efeect of place, product completeness, and service on the purchasing on mini market Sinar Jaya. In the research using a method of collecting data with a questionnaire with the number of samples 100 respondents, the sample accidental use sampling techniques and methods of analysis of data used in this research in linier regression worship of idols. The result of this research shows that all the independent variable that is a place, completeness products, and service has links positive in line against the dependent variable for which is purchasing decisions. The testing of hypotheses using test t show that the three independent variable for which researched proved to be significantly affect the decision purchase. The results showed that in partial positive and significant impact location on the decision purchase at the mini market Sinar Jaya for 28,9%. Partially affect the product completeness of 29,7% of the decision purchase, Partially affect the service of 44,3% of the purchase decision. Influence of location, product completeness, and services simultaneously positive and significant effect on the purchasing decisions at the mini market Sinar Jaya of 39,7%. Then through the f can be known that in the three joint of a variable that affected purchase decision. Figures adjusted r square worth 0,397 show that the independent variable can explain 39% decision the purchase of the remaining 61% by other variables out of one variable are used in this research